Structural characteristics, bioavailability and cardioprotective potential of saponins - Deepika Singh; Prabir Kumar Chaudhuri (Integrative Medicine Research)
Cardiovascular diseases are the leading cause of death, accounting about 31% deaths globally in 2012. The major risk factors causing cardiovascular diseases are coronary atherosclerosis, hyperlipidemia, myocardial infarction, and stroke. The dominating cause of cardiovascular diseases is accredited to our modern lifestyle and diet. Medicinal plants have been used for the prevention and treatment of cardiovascular diseases from centuries. The in built chirality and chemical space of natural products have been playing an important role in providing leads and templates for pharmacophore synthesis. This review highlights one of the important naturally occurring class saponins and their role in cardioprotection along with structural characteristics and pharmacological effects such as antioxidant, Ca2+ ion regulation, antiapoptotic, antiatherosclerosis, antihyperlipidemic, hypocholesterolemic, angiogenic, vasodilatory, and hypotensive. The characteristic cholesterol lowering, hemolytic, and anticoagulant properties of the saponins prompted us to select as one of the natural products class for cardioprotection. This review covers the most updated information on saponins related to their cardioprotective effects, mechanism of action, bioavailability, and structure activity relationship. Keywords: Bioavailability, Cardioprotective activity, Saponins, Structure activity relationship